2020
DOI: 10.5811/westjem.2019.11.44597
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Trauma Scene and Transport Times for Pediatric and Adult Patients

Abstract: Introduction: Increased out-of-hospital time is associated with worse outcomes in trauma. Sparse literature exists comparing prehospital scene and transport time management intervals between adult and pediatric trauma patients. National Emergency Medical Services guidelines recommend that trauma scene time be less than 10 minutes. The objective of this study was to examine prehospital time intervals in adult and pediatric trauma patients. Methods: We performed a retrospective cohort study of blunt and penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…Children represented 3.7% of EMS missions and had significantly shorter OST. Our study is consistent with multiple studies that found children’s OST to be significantly shorter than adults 27 28. In our study, elderly patients had by far the longest median OST.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Children represented 3.7% of EMS missions and had significantly shorter OST. Our study is consistent with multiple studies that found children’s OST to be significantly shorter than adults 27 28. In our study, elderly patients had by far the longest median OST.…”
Section: Discussionsupporting
confidence: 93%
“…Although we look for explanations in Saudi EMS setting, the gender differences are not confined to our study. Our findings are in line with several studies from other countries which often found that women had a longer median or average OST compared with men 12 28 29 31 33 34. None of these studies investigated the impact of different sociocultural factors on spent time at the scene for patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although the reasons for a faster response with African American patients are unclear, this could be because African American populations tend to concentrate around urban centers, which have higher concentrations of EMS bases and proximity to hospitals. 24,25 On-scene time was 19±17 min, longer than the target 10 min on-scene time adopted by most EMS systems. This reflects a possibly prolonged extrication requirement and on-scene resuscitation attempt.…”
Section: Discussionmentioning
confidence: 90%
“…A study by Ashburn et. al., which examined EMS records of trauma patients in ve counties in North Carolina, found regional differences of up to 6 minutes in EMS on-scene time [27]. However, these regional differences are not well explored, although various complicating factors could account for these differences.…”
Section: Discussionmentioning
confidence: 99%